Reconstructing Electoral Legal Politics in Indonesia: A Critical Analysis of the Ambivalence of the Open Proportional System and Electoral Thresholds Post Constitutional Court Decision No. 55/PUU-XXII/2024 - Lisda Apriliani Sobirin; Muhamad Iqbal Ansori Firdaus; Ilman Napiah; Taufik Taufik; Fina Rosalina; Dian Hadiana (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
Indonesia's post reform electoral system was designed to strengthen popular representation but has paradoxically become an arena for elite interest contestation. This study critically analyzes the ambivalence of legal politics regarding the open proportional system and electoral thresholds, focusing on Constitutional Court Decision No. 55/PUU-XXII/2024. Employing doctrinal legal research with statutory, conceptual, and case approaches, the analysis examines Law Number 7 of 2017 and the Court's jurisprudence. The findings reveal a structural paradox: the system normatively recognizes popular sovereignty but practically restricts political competition through high thresholds that benefit political cartels and incentivize high cost politics. Furthermore, the Constitutional Court’s open legal policy doctrine frequently metamorphoses into a shield for the legislative oligarchy, evading substantive constitutional correction. Ultimately, this article proposes a comprehensive reconstruction of electoral legal politics, shifting the paradigm from democratic containment to electoral justice. This reconstruction demands normative threshold reforms, structural political funding improvements, and the application of strict scrutiny by the Constitutional Court to safeguard citizens' rights against oligarchic capture, ensuring genuine constitutional democracy and equitable political participation.